Studi Korelasional Motivasi Belajar dan Hasil Belajar Kalkulus Diferensial pada Mahasiswa Pendidikan Matematika - Khusna, Akhmad Qoidul; Supriyo, Supriyo (Indo-MathEdu Intellectuals Journal, 2026)
Differential Calculus is a cornerstone of the mathematics curriculum, yet its abstract nature often presents obstacles for pre-service teachers. Although academic success is frequently linked to motivation, significant achievement gaps persist even under uniform teaching conditions. This study aims to analyze the relationship between learning motivation and academic achievement in Differential Calculus among Mathematics Education students at Universitas PGRI Wiranegara. The research employs a quantitative approach with a correlational design involving a sample of 30 students. Data were collected through questionnaires and academic records, then analyzed using the Pearson Product Moment correlation test. The findings indicate a very weak relationship (r = 0,197) between motivation and final grades. These results suggest that in challenging subjects, cognitive prerequisites and external variables may have a stronger correlation than affective traits, thereby emphasizing the need for an instructional focus on foundational skills and cognitive methodologies